A rare case of persistent urogenital sinus in an adult woman associated with unilateral rudimentary horn with ipsilateral renal agenesis and contralateral dermoid cyst - Mohamed Ibrahim Amer (Iberoamerican Journal of Medicine, 2021)
Persistent urogenital sinus (PUGS) is an uncommon developmental cloacal anomaly, with Incidence of 0.6 in 10000 female births. Herein we depict the case of a 22-year of age lady who presented with Infertility for 16 months with dyspareunia and was found to have Persistent urogenital sinus associated with other urogenital anomalies as unilateral rudimentary horn with ipsilateral renal agenesis and contralateral dermoid cyst. The patient was successfully treated with the excision of the sinus, the rudimentary horn and the dermoid cyst.